THE RIGHT TO A GOOD AND HEALTHY ENVIRONMENT: Problems Of Implementation In Indonesia. - Ahmad Romsan (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
The integration of environmental rights into human rights in Indonesian Environmental Management Acts (EMAs) has taken 37 years after the 1972 Stockholm Declaration on Human Environment and 27 years after the Indonesian Government enacted the first EMA 1982. Although a lot of community environmental disputes have been brought before the District Courts during the period of the EMA1982 up to the EMA1997, the Courts’ decisions have dissatisfied the people. The nexus of constitutional rights, environmental rights and human rights in the realm of environmental human rights has remained uncertain since violation to environmental human rights cannot be brought before the Indonesian Human Rights Court as its jurisdictions only includes genocide and crimes against humanity. A crime against environmental rights is still excluded from the Human Rights Law No. 39 of 1999 as well as the Human Right Law No. 26 of 2000 on the Indonesia Human Rights Court. Hence, environmental human rights violation comes within the jurisdiction of the District Court. With all its strengths and weaknesses the District Court is the only recourse for community environmental disputes adjudication. In the interest of protecting people’s good and healthy environment, this paper suggests the establishment of a special environmental court under the General Court in Indonesia as a solution. Additionally, it also suggests the inclusion of a supplementary element to the crime against humanity in the Law No. 39 of 1999 on Human Rights and Law No. 26 of 2000 on Human Rights Court which is environmental rights violation.